Reshaping endoplasmic reticulum quality control through the unfolded protein response - Wiseman, R Luke; Mesgarzadeh, Jaleh S; Hendershot, Linda M (Molecular cell, 2022)
Endoplasmic reticulum quality control (ERQC) pathways comprising chaperones, folding enzymes, and degradation factors ensure the fidelity of ER protein folding and trafficking to downstream secretory environments. However, multiple factors, including tissue-specific secretory proteomes, environmental and genetic insults, and organismal aging, challenge ERQC. Thus, a key question is: how do cells adapt ERQC to match the diverse, ever-changing demands encountered during normal physiology and in disease? The answer lies in the unfolded protein response (UPR), a signaling mechanism activated by ER stress. In mammals, the UPR comprises three signaling pathways regulated downstream of the ER membrane proteins IRE1, ATF6, and PERK. Upon activation, these UPR pathways remodel ERQC to alleviate cellular stress and restore ER function. Here, we describe how UPR signaling pathways adapt ERQC, highlighting their importance for maintaining ER function across tissues and the potential for targeting the UPR to mitigate pathologies associated with protein misfolding diseases.